The possibilities of using riddles in working with older preschool children with mental retardation (message 2) - Kovalenko O. M., Brovina O. S. (Pedagogy, Psychology, Society, 2024)
The article presents data showing the possibilities of using riddles in working with children aged 6-7 years with mental retardation in preparation for the plot-role-playing game "In the store".
Keywords: задержка психического развития; старший дошкольный возраст; mental retardation; senior preschool age; загадки; riddles